The ethics of the Letter to Philemon - Tolmie, D. F. (Neotestamentica, 2020)
In this study, the ethics of the Letter to Philemon is investigated by means of an integrated model for interpreting the ethics of the New Testament (called an Organon) that was developed by Ruben Zimmermann. Five issues are addressed, namely (1) how moral significance is created in the letter; (2) which norms appear in the letter; (3) where these norms come from; (4) if a hierarchy of norms can be discerned in the letter; and (5) how the ethics of the letter can be appropriated for our current context(s). It is argued that in this letter moral significance is generated by means of an integrated “web of norms” consisting of norms such as “spiritual kinship” and “divine will,” and that this may be appropriated in a meaningful way for our times by means of a compliant reading, balanced by a resistant reading.